New Neotropical cleptoparasites in the genus Austrostelis (Hymenoptera: Megachilidae: Anthidiini) - Griswold, Terry (Journal of Melittology, 2025)
Three new species of cleptoparasites of the rare genus Austrostelis Michener & Griswold are described. Austrostelis mexicana Griswold n. sp. and A. costaricensis Griswold n.sp. represent a northern extension of the genus into Mesoamerica while A. bicolor Griswold n. sp. from Venezuela adds to our limited knowledge for northern South America. A key to the species from Mesoamerica and northern South America is provided.